Fractured soul : a novel - Mizubayashi, Akira, 1951- (HarperVia, 2023)
"Tokyo, 1938. An amateur quartet, led by the compassionate Yu, gathers to practice. Suddenly, their rehearsal is brutally interrupted by military police. In the ensuing skirmish, Yu's violin is smashed while his son, Rei, witnesses his father's arrest. He will never see him again. Salvaging his father's instrument, Rei escapes thanks to a mysterious lieutenant. Paris, 2003. Raised in France, Rei-now Jacques-has dedicated his life to the broken violin's repair: studying music, becoming an apprentice, and, eventually, a luthier. However, despite his effort to rehabilitate the damage of years ago, he struggles to reconcile his past with the present. Yet, when a world-class violinist, connected to the lieutenant that helped him as a boy, appears, Jacques' past is rekindled and he perseveres in a final bid to heal. Fractured Soul is a parable of what once was lost and what there stands to be gained-a story of immense beauty and ferocious courage"--